Improving Spatial Visual Intelligence in Merauke Kindergarten Group B Children Using Finger Painting Techniques - Cristiana Normalita de Lima,; Dharma Gyta Sari Harahap,; Muh. Rafi'y,; Ferry Irawan,; Rivaldo Paul Telussa, (Technium Social Sciences Journal, 2023)
Drawing and painting activities. The finger painting technique is one type of activity that can be done to develop visual-spatial skills. The study included group B children from Merauke District Kindergartens. Classroom Action Research (CAR) was used, and it was carried out in two cycles. Three meetings were conducted in each cycle. This study included 200 students from five kindergartens in the Merauke District, including Pembina State Kindergarten, Yapis Kindergarten, ABBA WASUR II Kindergarten, and AL-FATAH Kindergarten. Techniques for collecting data include direct observation, practice, and documentation. Analyze descriptive data. The study's findings revealed that employing the finger painting technique, children's visual spatial intelligence increased at each meeting, with cycle I reaching 20 children. (10%), up to 180 children in cycle II (90%) with the criteria Developing According to Expectations.